Feasibility of enabling self-management and coping with arthritic pain using exercise (ESCAPE-Pain) programme for knee osteoarthritis in Malaysia - Che Hasan, Muhammad Kamil; Stanmore, Emma; Todd, Chris (Wiley Online Library, 2018)
Background/Purpose: In Malaysia around one in ten older people are diagnosed with osteoarthritis (OA), with the knee being one of the most commonly affected areas. This can lead to functional limitations, impaired activities of daily living and reduced quality-of-life. Our systematic review of the literature concludes that a programme integrating exercise, education and active coping strategies, known as Enabling Self-management and Coping with Arthritic Pain using Exercise (ESCAPE-pain) provides the best evidence for implementation. Thus, this study aims to evaluate the feasibility of the ESCAPE-pain programme among patients with knee OA in the Malaysian healthcare context.